2010
DOI: 10.1103/physrevb.81.054446
|View full text |Cite
|
Sign up to set email alerts
|

Exchange interactions and Curie temperatures in Cr-based alloys in the zinc blende structure: Volume- and composition-dependence from first-principles calculations

Abstract: We present calculations of the exchange interactions and Curie temperatures in Cr-based pnictides and chalcogenides of the form CrX with X=As, Sb, S, Se and Te, and the mixed alloys CrAs50X50 with X=Sb, S, Se, and Te. The calculations are performed for Zinc Blende (ZB) structure for 12 values of the lattice parameter between 5.44 and 6.62Å, appropriate for some typical II-VI and III-V semiconducting substrates. Electronic structure is calculated via the linear muffin-tin-orbitals (LMTO) method in the atomic sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…(3) or (4) when, in addition to the robust moments on the magnetic atoms, there are induced moments on apparently non-magnetic atoms, interstitial spaces, or, in case of the LMTO method, empty spheres. This problem has been discussed in detail in our previous publication 35 and references cited therein. As shown by Sandratskii et al, 33 the calculation of T c using RPA is considerably more involved even for the case where only one secondary induced interaction needs to be considered, in addition to the principal interaction between the strong moments.…”
Section: Compoundsmentioning
confidence: 98%
See 1 more Smart Citation
“…(3) or (4) when, in addition to the robust moments on the magnetic atoms, there are induced moments on apparently non-magnetic atoms, interstitial spaces, or, in case of the LMTO method, empty spheres. This problem has been discussed in detail in our previous publication 35 and references cited therein. As shown by Sandratskii et al, 33 the calculation of T c using RPA is considerably more involved even for the case where only one secondary induced interaction needs to be considered, in addition to the principal interaction between the strong moments.…”
Section: Compoundsmentioning
confidence: 98%
“…35,36 Here, i and j are site indices, e i is the unit vector pointing along the direction of the local magnetic moment at site i, and J ij is the exchange interaction between the moments at sites i and j. The calculations are based on a mapping procedure due to Liechtenstein et al [37][38][39] This method was later extended to random magnetic systems by Turek et al, using CPA and the TB-LMTO method.…”
Section: Exchange Interaction and Curie Temperaturementioning
confidence: 99%
“…In fact, it is just the band energy, not the total energy, which is considered in the mapping, by appealing to the so-called "magnetic force theorem" (see Ref. 25 and references therein). For finite temperature (T = 0) calculations, as would be appropriate for the DLM reference state, one needs to consider the mapping of the free energy F = U − T S, where U is the internal energy and S is the entropy.…”
Section: Formalismmentioning
confidence: 99%
“…Similar calculations have also been carried out for the intermetallic compound GdAl 2 24 and for Cr-based compounds in the zincblende structure. 25 A systematic theoretical study of the pressure-dependence of T c in Heusler alloys was carried out recently by Sasioglu et al, 26 where the experimentally observed increase of T c with pressure 9,11 in Ni 2 MnSn was reproduced correctly, albeit only qualitatively so. There exists some other studies of Heusler alloys in which the dependence of the exchange integrals on volume contraction and expansion 17,[27][28][29] was explored.…”
Section: Introductionmentioning
confidence: 99%
“…Since Akinaga et al 1 predicted theoretically and confirmed experimentally in 2000 the half-metallic (HM) ferromagnetism in zinc-blende (ZB) CrAs, transition-metal pnictides and chalcogenides (TM-PCs) with ZB structure have attracted increasing research interest in the past ten years, because most of this class of compounds were predicted to HM ferromagnets, [2][3][4][5][6][7][8][9][10] i.e., compounds for which only one spin channel is metallic, resulting in 100% spin polarization at the Fermi level. The half-metallicity and the comparable lattice structure with conventional binary semiconductors make ZB TM-PCs promising candidates of spininjector materials in spintronic devices.…”
Section: Introductionmentioning
confidence: 99%